Cohousing. Estratégias de desenho e escalas do habitar em comum - Marta Raquel Pereira Costa da Silva Vitorino (2017)
The present dissertation is a research on the design mechanisms adopted inthe confguration of the common and the private domestic spaces in Cohousing.In the absence of a more detailed and comparative work on designingbuilding solutions of this nature, this work, seeking to reconcile the intrinsic scope of thissubject with the feld of design and architecture, establishes a 'new insight' of thedynamics of the meeting, coexistence, and life in contemporary Cohousingcommunities. Through the redesign of 12 international case studies built between 2003and 2015, it was possible to identify, by the analyses of their drawing peculiarities andsimilarities, different design strategies according to common patterns of how the spatial,formal and social results are achieved and shaped by this shared form of living.The investigation ends with a refection on the previous analysis, clarifying thecohabitation scale as a material of space, as an instrument to the defnition ofCohousing, creating, by the combination of elements and architectural tools, a greateror lesser intensity of sharing and privacy in communities of this nature.